Kinematic and kinetic analysis of throwing a straight punch: the role of trunk rotation in delivering a powerful straight punch - Tong-Iam, R.; Rachanavy, P.; Lawsirirat, C. (Journal of Physical Education and Sport, 2017)
Powerful straight punches create strategic advantage for boxers. However, there is discrepancy in theoretical and practical understandings of how to deliver powerful straight punches. This paper attempted to investigate the role of trunk rotation in straight punches. Trunk rotation was suggested as a critical component in delivering straight punches. However, no research has yet to address the importance of trunk rotation in straight punches. Three professional boxers who competed regularly in Muay Thai and boxing were recruited in this study. Both kinematic and kinetic analysis were performed. Straight punches were dissected into stages using ground reaction force. The result showed straight punches had 3 stages, i.e., (1) starting position, (2) lead toe off, and (3) lead toe in. The results suggested that the final stage, lead toe in, was the most important in delivering powerful straight